EXTRACTION AND ACID HYDROLYSES OF FRESH JERUSALEM ARTICHOKE INULIN FOR FRUCTOOLIGOSACCHARIDE PRODUCTION - & Abood, Alabadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to produce fructooligosaccharide (FOS) from fresh jerusalem artichoke (JAT) inulin which was extracted by conventional method (hot water extraction) at two different temperature (80˚C & 90˚C\ 90 min). JAT slices were mixed with distilled water at (1 : 5) (w : v) ratio, the obtained extract purified and concentrated to 32˚Brix, then mixed with acetone (1 : 3) (v : v), kept at 4˚C for 24 h., centrifuged at 10000g/ 15 min., and the precipitate dried at 55˚C. Acid hydrolysis of the dried inulin was carried out at three different pH values being (1.5, 2.5 & 3.0) at 85˚C using citric acid (10 %), aliquot of inulin hydrolysate were taken after (5, 10, 15, 20, 25 & 30) min. for qualitative analysis using TLC and RP-HPLC. The results revealed that there were no significant differences in the yield of extracted inulin (33.86, 33.67 %) and extraction efficiency (80.62, 80.17 %) between the extraction at 80˚C and 90˚C\ 90 min. respectively. The optimum condition for acid hydrolysis of the obtained inulin was at pH 2.5 after 15 min at 85˚C. The qualitative analysis for hydrolysate using TLC and RP-HPLC showed that the degree of polymerization (DP) of inulin ranged from (2 - 35) unit and for FOS ranged from (2 – 9) units.